Carbon dot targeting to nitrogen signaling molecules for inhibiting neuronal death. Issue 11 (26th February 2020) - Ouyang, Lufei; Mu, Xiaoyu; Wang, Junying; Li, Qifeng; Gao, Yalong; Liu, Haile; Sun, Si; Ren, Qinjuan; Yan, Ruijuan; Wang, Jingya; Liu, Qiang; Sun, Yuanming; et al.
Abstract : Ultrasmall carbon dot with targeting ability to nitrogen signaling molecules inhibit neuronal death by regulating the activity of endogenous enzymes. Abstract : Free radical-induced oxidative damage and nitrosative stress have been identified as key factors in neuroinflammation responses after traumatic brain injury (TBI), with which reactive oxygen and nitrogen species (RONS), especially nitrogen signaling molecules, are strongly associated. Here, we prepared ultrasmall carbon dot (CD) by using a simple and facile method. In vitro assessment experiments show that the antioxidative CD exhibits an ultrahigh target-scavenging effect for nitrogen signaling molecules, especially the highly reactive ˙NO and ONOO − . However, CD can only partially eliminate conventional oxygen radials such as O2 ˙ − and ˙OH, indicating CD has a preference for RNS modulation. Moreover, in vitro cell experiments and in vivo mice experiments reveal that CD can reduce the reactive oxygen species (ROS) level and lipid peroxidation, enhance superoxide dismutase (SOD) activity and GSSG level, and further improve the survival rate of neuron cells and TBI mice. These results declare that antioxidative CD could serve as an effective therapeutic for TBI.